(untitled) (Research, Society and Development, 2025)
This study aimed to describe the health needs of university employees through nursing consultations in a school office and to present the "Prevention is Care" product, developed to improve immunization adherence in the workplace. This observational, descriptive, and quantitative study monitored employee care in the nursing school office of a private university from November 2021 to December 2022. Twenty-two employees participated. Most were female, self-identified as Black or mixed race, and over 40 years of age. The two most common comorbidities were systemic arterial hypertension and diabetes mellitus. Low vaccination coverage for some vaccines was observed, which is the most significant vulnerability. Nursing consultations demonstrated potential for identifying health vulnerabilities and proposing targeted interventions, such as the "Prevention is Care" form, to strengthen worker health promotion actions in the university environment.